The photosystem I assembly apparatus consisting of Ycf3–Y3IP1 and Ycf4 modules - Sreedhar Nellaepalli (Nature Portfolio, 2018)
Photosystem I is a large multiprotein complex embedded in the chloroplast thylakoid membrane. Here the authors provide evidence for a modular assembly process, whereby Ycf3 facilitates assembly of the reaction center, while Ycf4 incorporates peripheral core and light harvesting complex subunits to the reaction center.